Body odors (even when masked) make you more emotional: behavioral and neural insights - Cecchetto, Cinzia (2019)
Morality evolved within specific social contexts that are argued to shape moral choices. In turn, moral choices are hypothesized to be affected by body odors as they powerfully convey socially-relevant information. We thus investigated the neural underpinnings of the possible body odors effect on the participants' decisions. In an fMRI study we presented to healthy individuals 64 moral dilemmas divided in incongruent (real) and congruent (fake) moral dilemmas, using different types of harm (intentional: instrumental dilemmas, or inadvertent: accidental dilemmas). Participants were required to choose deontological or utilitarian actions under the exposure to a neutral fragrance (masker) or body odors concealed by the same masker (masked body odor). Smelling the masked body odor while processing incongruent (not congruent) dilemmas activates the supramarginal gyrus, consistent with an increase in prosocial attitude. When processing accidental (not instrumental) dilemmas, smelling the masked body odor activates the angular gyrus, an area associated with the processing of people's presence, supporting the hypothesis that body odors enhance the saliency of the social context in moral scenarios. These results suggest that masked body odors can influence moral choices by increasing the emotional experience during the decision process, and further explain how sensory unconscious biases affect human behavior.